IMPLEMENTASI PENDEKATAN KONTEKTUAL SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA MTs PADA MATERI SPLDV - Risma Yanti; Teti Sobari; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to determine the improvement of student learning outcomes with the contextual approach applied by the teacher in the learning of mathematics in the classroomThe type of research which used is classroom action research (PTK) through two cycles consisting of two meeting in every cycle. The procedures performed in each cycle are planning, implementation, observation, and reflection. Subjects in this study were students of class VIII in one of the MTs State in Cimahi as many as 31 people, consisting of 14 men and 17 women. The results showed that: (1) increase student learning outcomes indicated by the increase in cycle I the average value of the 58,87 with the percentage 32,26% and the cycle II theaverage score achieved by 82,07 with the percentage of 77,42%; (2) the activity of the students and the teacher in the learning has been quite good from every cycle, however there is still a shortage that can not be repaired.Â